National Catholic Reporter at Fifty: The Story of the Pioneering Paper and Its Editors - Jones, Arthur (Rowman & Littlefield Publishers, 2014)
National Catholic Reporter at Fifty tells the story of the award-winning Catholic paper the National Catholic Reporter (NCR) in the lead-up to NCR’s 50th anniversary in October 2014. Founded during the Second Vatican Council, NCR has been a powerful progressive voice in the Catholic Church and has broken a number of challenging stories—first covering the nationwide clerical pedophilia crisis, publishing the secret Papal Birth Control Commission report that recommended ending the ban on birth control (which Pope Paul VI overrode), and the scandal that African priests were seducing or raping nuns because they were AIDS-free on a continent that wasn’t. National Catholic Reporter at Fifty takes readers through NCR’s highs and lows, with a focus on its important editors and key themes—race and poverty, peace/foreign policy, women’s issues, sexuality, and the church/papacy.